Associations of follicle-stimulating hormone and luteinizing hormone with metabolic syndrome during the menopausal transition from the National Health and Nutrition Examination Survey - Chen, Yongjie; Wang, Caihong; Sun, Boran; Wang, Bingyi; Lu, Xinlin; Gao, Bei; Cao, Ye; Zhou, Jiangtao; Liu, Xuewei (Frontiers in Endocrinology, 2023)
Background The increased risk of metabolic syndrome (MetS) during the menopausal transition might partly attribute to the changes in follicle-stimulating hormone (FSH) and luteinizing hormone (LH). However, few studies were conducted to examine the associations of FSH and LH concentrations with MetS at the full range of reproductive aging, especially in the US population. The aim of this study is to examine the associations of FSH, LH, and LH/FSH ratio with the risk of MetS and severity score in the US women. Methods Data were derived from the National Health and Nutrition Examination Survey. Women aged from 35 to 60 years were eligible. MetS was defined as having at least 3 of the following: a waist circumference ≥ 88 cm, a triglycerides level ≥ 150 mg/dL, a high density lipoprotein < 50 mg/dL, a systolic blood pressure ≥ 130 mm Hg or a diastolic blood pressure ≥ 85 mm Hg or taking hypertension medications, or a fasting plasma glucose level ≥100 mg/dL or taking diabetes medications. The MetS severity score was calculated according to race/ethnicity- specific equation. Results There were 3,831 women included in this study. Increases in serum FSH and LH levels per 1 SD were separately linked to a 22.6% (OR: 0.774; 95% CI: 0.646, 0.929; and P= 0.006) and 18.5% (OR: 0.815; 95% CI: 0.690, 0.962; and P= 0.006) lower risk of MetS only in postmenopausal women. Meanwhile, increases in serum FSH and LH levels per 1SD were associated with a decrease of -0.157 (95% CI :-2.967, -2.034) and -0.078 (95% CI: -2.688, -1.806) MetS severity score in perimenopausal women and -0.195 (95% CI: -2.192, -1.023) and -0.098 (95% CI:-1.884, -0.733) in postmenopausal women. However, LH/FSH ratio had no connections with the risk of MetS and MetS severity score across the menopausal transition. Conclusions Elevated serum FSH and LH levels, but not LH/FSH ratio, were associated with a lower risk of MetS and MetS severity score, especially in postmenopausal women. Therefore, serum FSH and LH levels might be efficient predictors for screening and identifying women at risk of MetS across the menopausal transition.